Vrtičkarstvo v Ljubljani - Jamnik, Brigita (Geografija Slovenije, 2009)
Garden-plot areas spontaneously developed and were distributed across the entire flat area of Ljubljana. Due to a new, more urban lifestyle and a policy change by the city authorities, the area of garden plots fell considerably at the end of the twentieth and the beginning of the twenty-first centuries. The most recent analysis of plot gardening in the City of Ljubljana, which surveyed 302 plot gardeners, showed that the overall infrastructure available in garden-plot areas is relatively poor. This activity is mainly practiced by older and lower-income people, most of whom live in apartment buildings. Due to pesticide residues and heavy metals in the soil and produce, as well as groundwater contamination, plot gardening poses a threat to public health and the environment. The 2008 Draft Ljubljana Zoning Implementation Plan foresees a reduction in the total area of plot-gardening areas by nearly half~however, even the planned community garden plots include some that do not meet the minimum location standards. Some garden-plot areas are problematic primarily because they are located close to major traffic routes. In the future, plot gardeners will have to be more systematically informed and educated about proper and safe use of fertilizers and pesticides.